Prognostic Value of Surfactant Protein D and Biochemical Markers in BALF and Plasma of ARDS Patients Undergoing Mechanical Ventilation: Prognostic Role of SP-D and Lactate in ARDS - Han, Hu; Zhang, Litao; Guo, Hui; Xu, Xin; Zhao, Xi (Journal of Medical Biochemistry, 2025)
Background: Surfactant protein D (SP-D) and circulating exosomes have emerged as potential biochemical indicators of lung injury severity in acute respiratory distress syndrome (ARDS). This study aimed to evaluate the prognostic value of SP-D levels and selected biochemical parameters in bronchoalveolar lavage fluid (BALF) and plasma among ARDS patients receiving mechanical ventilation. Methods: A total of 103 mechanically ventilated ARDS patients were enrolled between February 2020 and February 2023. Patients were classified into survival (n=59) and death (n=44) groups based on 28-day mortality. On the day of diagnosis, SP-D and exosome levels in BALF and plasma, along with pH, lactate, and oxygenation-related indices, were measured and analyzed for prognostic relevance. Results: SP-D levels in both BALF and plasma were significantly higher in non-survivors (P<0.001), while exosome levels did not differ significantly. The death group also showed elevated lactate and lower pH levels (P<0.05). ROC analysis demonstrated high predictive value for SP-D in BALF (AUC=0.804) and plasma (AUC=0.864), as well as for lactate and oxygenation indices. A combined biomarker model yielded an AUC of 0.883 for predicting 28-day mortality. Conclusion: SP-D concentrations in BALF and plasma, along with lactate and acid–base markers, serve as valuable biochemical predictors of short-term prognosis in ARDS patients undergoing mechanical ventilation.